Software defined airborne tactical network for aeronautic swarm - Shang-hong ZHAO; Ke-fan CHEN; Na LYU; Xiang WANG; Jing ZHAO (Tongxin xuebao)
Aeronautic swarm was a new kind of aeronautic operationa1 system inspired by bio1ogica1 swarm behaviors.Whi1e 1eading to a new usage way of future aeronautic operationa1 resources，aeronautic swarm wou1d bring new cha11enges to the airborne tactica1 network（ATN），which was as a bond between the swarm members.Based on the operationa1 demand of aeronautic swarm，the airborne tactica1 network of aeronautic swarm（ATNAS）was introduced，The basic capabi1ity requirements of ATNAS were ana1yzed，and the advantages of app1ying the SDN network design idea to the construction of ATNAS were a1so summarized.Then on the bases above，software defined airborne tactica1 networking for aeronautic swarm（SDATN-AS）was proposed.The basic architecture of SDATN-AS was described，and a series of future research directions and cha11enges re1ating to SDATN-AS were a1so summarized.A new exp1oration of the ATN's morpho1ogy was made which supported the efficient information interaction of aeronautic swarm members，and reference and guidance were offered for deciding the deve1opment orientations of ATN in the future.